PENGEMBANGAN MEDIA LATIHAN JURUS TUNGGAL IPSI BERBASIS GOOGLE SITES DI EKSTRAKURIKULER SDN 3 WONOKERSO DAN SDN 1 PAKISAJI - Mukhlisin, Muhamad; Supriyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Research in order to develop and evaluate IPSI single stance training media based on Google Sites applications to support pencak silat learning at the elementary school level. This media is designed to provide visual guidance as well as basic single stance material that is easily accessible and understood by students. The research method uses development stages which include analyzing needs, designing media, developing, implementing, and evaluating media. Expert validation was conducted by elementary school sports teachers, East Java national pencak silat trainers, and educational technology lecturers. The results of the validation showed that this training media was feasible to use with some minor improvements in visual aspects and interactive features to increase student engagement. Two-stage small and large group trials showed positive responses, where students were more motivated and found it helpful in understanding the movements and techniques of the single stance. This media is considered relevant to be applied in elementary schools with advantages in accessibility and interactivity. Some constraints were found, such as limited devices and internet connection in some schools. This study suggests periodic updates to the media, training for teachers, and development of additional interactive features to improve the effectiveness of pencak silat learning in elementary schools.